The epistemic properties in a typical engineering science course and its relation to student success: a case study - Awodele, Williams Abayomi (Department of Electrical Engineering, 2019)
One of the problems facing South African higher education is the low throughput rates, in particular for students who are educationally disadvantaged. Research studies point to various factors that impact student success, such as educational background and various socio-economic factors. Universities have attempted to address the problem by making available various academic support programmes for entering students. This research project looks at the nature of the knowledge content of the various engineering courses in a university curriculum and its potential impact on students’ performance which might result into low throughput rate. The study, therefore, investigates the epistemic properties of a typical third-year engineering science course in the department of electrical engineering at the University of Cape Town, as a case study. The researcher used the annual departmental results between 2005 and 2013 to identify a specific engineering science course that had repeated high failure rates for ex-ASPECT students compared to the rest of the class. The course lecturer was interviewed and the transcript of the interviews served as the data used in this project. The data generated from the interviews were analysed using the theoretical concept of semantics (semantic gravity and semantic density) which is one of the dimensions of Legitimation Code Theory (LCT) developed by Karl Maton. The analysis of the data uncovered two main issues. Firstly, there is a wide semantic range in the required knowledge and skills in order for the students to be successful in the course. Secondly, the analysis reveals that there is a link between semantic gravity and semantic density in terms of the knowledge that students need to have, understand and master in order to be successful in the course. This study raises the possibility of the epistemic properties of engineering science knowledge being a contributing factor to the underperformance of the ex-ASPECT students in the department of electrical engineering of the University of Cape Town. Suggestions are then given for further studies on finding solutions to the identified problems.